Etnomatematika: Identifikasi Unsur Matematis pada Struktur Utama Bangunan Candi Tikus Kabupaten Mojokerto - Eko Sugandi; Syukron Maftuh; Lydia Lia Prayitno; Ninik Mutianingsih (Journal on Education, 2025)
This research to show the relationship between mathematics and the structure of the Tikus Temple building, Mojokerto Regency. This research aims to explore parts of Tikus Temple that contain mathematical concepts. The building structure is the focus of this research. The method used in this study uses ethnographic methods with data collection techniques using ethnographic principles such as observation, interviews, documentation, and making field notes. The results showed that ethnomathematics exploration of the structures of the Tikus Temple contains cultural values full of history and mathematical concepts in the material of geometric transformations, plane shapes, and spatial shapes.